Community Service "Assertive Communication Training To Enhance Assertive Communication Among Teenagers At The Puteri Kerahiman Orphanage In Jayapura" - Paulus Satyo Istandar Tan; Angela Marciana Ayu Saptarina Maturbongs (Eduvest - Journal of Universal Studies, 2024)
This activity aims to improve assertive communication skills among teenagers at the Putri Kerahiman Jayapura orphanage. Assertive communication is the ability to speak clearly, express opinions, and express needs without causing harm to oneself or others. Teenagers need to improve assertive communication skills so that they can build effective relationships with other people and protect themselves from the temptation of juvenile delinquent behavior. This activity is carried out in the form of assertive communication training using communication games as media. It is hoped that through this activity, teenagers living in orphanages can develop assertive skills, such as having the courage to express their thoughts and feelings clearly and honestly without offending other people’s feelings.